Chassez les stéréotypes, ils reviennent au galop ! Choix atypiques de formation professionnelle et différenciation des groupes de sexe - Séverine Rey; Mélanie Battistini (Éducation et Socialisation)
Vocational training choices remain very much influenced by gender representations and norms. This article is based on data produced through researching atypical choices – from a gender perspective – in vocational training at tertiary level in French-speaking Switzerland. We analyze the experiences of people who have made such a choice: women in engineering and men in the health sector. We focus on the one hand on reactions from theirs peers, teachers and in the workplace; and on the other, on the strategies used by trainees to fit into their training and work environments. Our findings show that despite the possibility offered by atypical career choices for challenging gender norms, a gendered differentiation of individuals occurs, thus reaffirming traditional gender categories.